High Proline Content of Bacteria-Sized Particles in the Western North Pacific and Its Potential as a New Biogeochemical Indicator of Organic Matter Diagenesis - Takasu, Hiroyuki; Nagata, Toshi (Frontiers in Marine Science, 2015)
Amino acid (AA) compositions were determined for bacteria-sized particles and particulate organic matter (POM) collected in offshore regions of the western North Pacific. The L-proline content of bacteria-sized particles was remarkably high, accounting for 46 ± 10% (mean ± SD, n =3) of the total quantifiable AA (11 L-AAs and 2 D-AAs were quantified). The L-proline content was much higher than the corresponding values determined for isolated enteric and marine bacterial strains (2–9%). In POM, the L-proline content was low (<5% of total AA) in the upper layer (10–200 m), whereas it was high (20–26% of total AA) at a depth of 1000 m and was accompanied by the enrichment of D-enantiomers of AAs. L-proline enrichment in bacteria-sized particles and deep-water POM suggests a potential use of the L-proline content (mole%) as a new biogeochemical indicator of organic matter diagenesis.